Chitosan, a natural ligand for sustainable and environmentally benign asymmetric transfer hydrogenations - Kolcsár Vanessza Judit; Szőllősi György; International Symposium on Analytical and Environmental Problems (25.) (2019) (Szeged) (2019)
The transfer hydrogenations are convinent methods of obtaining chiral alcohols by enantioselective catalytic reactions. Catalytic methods suit most of the environmental requirements, though most of the chiral catalysts are made of synthetic ligands and are used in organic solvent. Natural ligands have a great potential to meet more requirements particularly if the solvent could be changed to water-based mixtures. We have studied the transfer hydrogenation of prochiral ketones catalyzed by an in situ prepared Ru-chitosan complex in aqueous media. The reaction of acetophenone and its substituted derivatives resulted in good enantioselectivities. Furthermore, to our delight in the reduction of several cyclic ketones over 90%, enantiomeric excesses were obtained, reaching up to 97% in the transfer hydrogenation of heterocyclic 4-chromanone or 4-thiochromanone derivatives. Based on these experiments, several N containing ketones were reduced in the above catalytic system. The results show that the position of the N atom and the number of its substituents influences the reached conversion and ee. Some of the N containing derivatives with the proper structure was transformed with high enantioselectivity (88-95%). The pre-prepared Ru-chitosan complex provided identical results even after several months’ storage without special precautions. With the comparison of the characterisation of the complex and the results of the transfer hydrogenations, we determined a possible complex and transition state structure. In conclusion the chiral catalyst prepared from a natural, inexpensive, readily available chiral ligand is a convenient alternative of the synthetic ligands and may be applied in environmentally friendly and sustainable processes for preparing optically pure chiral alcohols.